Existence and Uniqueness of Solutions and Lyapunov-Type Inequality for a Mixed Fractional Boundary Value Problem (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, a Lyapunov-type inequality for a linear differentialequation involving right Riemann-Liouville and left Caputo fractional derivatives under Sturm-Liouville boundary conditions is established. Furthermore,the existence of solutions for the corresponding nonlinear differential equationis obtained by fixed point theorems.
Keywords: Fractional derivative; Lyapunov-type inequality; Fixed point theorem.